Energy management, supply and conservation - Beggs, Clive (Elsevier Butterworth-Heinemann, 2009)
Energy - its source, security, price, and the efficiency of its use, are increasingly important issues for a diverse range of people. 'Energy: Management, Supply and Conservation' is a comprehensive text dealing with the theory and practice of the supply of energy, energy management and auditing, and the design of sustainable energy facilities. It considers the systems needed to create low-energy, sustainable buildings, including passive solar design, energy-efficient heating and air-conditioning, and combined heat and power. In addition the book includes substantial sections on renewable energy, transport energy, and energy economics. This new edition includes the latest in alternate-energy technology, for example wind turbines and solar panels as well as updating important energy values and statistics.-The book's readable style, along with its many figures, tables and worked examples make it an ideal text for courses on energy management, environmental engineering, architectural engineering and building services engineering. It will also be useful as a definitive handbook for professionals in the environmental, construction, utilities and facilities management sectors, as well as being of interest to those involved in sustainability economics and environmental policy making. Clive Beggs is Professor of Medical Technology at the University of Bradford. He is both a mechanical engineer and a biomedical scientist, who for many years has had an interest in ways in which energy is utilized and consumed. He is an expert in the fields of energy management and low energy building design, with many years experience of the design and installation of mechanical services within the construction industry.-He is a well known international speaker and is author of many scientific papers on low energy and environmentally friendly building design. He is a holder of the CIBSE Carter Bronze Medal for his work on desiccant cooling. * Understand energy issues effecting the built environment such as cost, supply, taxation and policy * How to monitor, manage and avoid waste energy * Worked examples showing how to calculate key energy factors.